Cement-based shield synchronous grouting material and preparation method thereof
By using gas induction agents and additives such as α-olefin sodium sulfonate and cocamidyl succinate in shield tunnel construction, the density and consistency of cement-based grouting materials are reduced, and cement consumption and pipe sheets are solved. The problem of floating has achieved efficient, energy-saving and environmentally friendly construction results.
Patent Information
- Application Number
- CN202411280562.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-13
AI Technical Summary
In shield tunnel construction, traditional cement-based synchronous grouting materials consume a large amount of cement, resulting in an increase in carbon emissions and the pipe sheets are prone to float, resulting in construction problems.
Using sodium α-olefin sulfonate and cocamidosulfonate as gas induction agents, combining pentyric acid and sodium carboxymethylcellulose, as well as nanosilica, reduce the density of grouting slurry, increase fluidity and Gas content to prevent bubbles from aggregating and improve compressive strength.
It significantly reduces the amount of cement used, reduces carbon emissions, solves the problem of pipe sheet floating, improves the fluidity and compressive resistance of grouting materials, saves the grouting amount per ring, and maintains good compressive strength.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of cement, and more specifically, to a cement-based shield synchronous grouting material and a preparation method thereof. Background Art
[0002] With the continuous development and improvement of my country's infrastructure construction, more and more projects use shield method to build railway tunnels, highway tunnels and municipal tunnels. In order to control the ground subsidence caused by shield excavation and protect the adjacent existing structures, during the shield machine excavation, the cutter head excavation diameter is about 100-140mm larger than the outer diameter of the pipe segment, and an annular gap is formed between the two. The excavation process requires synchronous grouting and filling. Synchronous grouting materials are a large amount of material consumption in shield tunnel projects. At present, cement-based mortar is mostly used for synchronous grouting materials in shield tunnel projects.
[0003] In the context of large-scale infrastructure construction, cement materials are in great demand in engineering. The use of traditional shield tunnel cement-based synchronous grouting materials requires a large amount of cement gelling materials. Summary of the invention
[0004] In order to reduce the amount of cement used in the synchronous grouting material during the shield tunneling process, the present application provides a cement-based shield synchronous grouting material.
[0005] In the first aspect, the present application provides a cement-based shield synchronous grouting material, which adopts the following technical solution: A cement-based shield synchronous grouting material comprises the following raw materials in parts by weight: 170-190 parts of cement, 760-780 parts of sand, 240-260 parts of fly ash, 50-60 parts of bentonite, 330-370 parts of water and 0.5-2 parts of air entraining agent, wherein the air entraining agent comprises sodium alpha-olefin sulfonate and cocoamido succinate.
[0006] By adopting the above technical solution, the present application introduces an air entraining agent into the cement-based shield synchronous grouting material. The addition of the air entraining agent introduces a large number of non-continuous tiny closed bubbles into the fresh slurry. The presence of the tiny bubbles plays a ball-like role in the slurry, improves the fluidity of the slurry, and reduces the density of the synchronous grouting material, thereby reducing the amount of cement used for the same volume of grouting material, thereby reducing the carbon emissions generated by consuming cement; in addition, since the segments are wrapped by the grouting slurry, the overall or partial floating of the segment lining often occurs during the construction of the shield tunnel, which ultimately leads to the segment misalignment, cracks, and even axis deviation. Due to the addition of the air entraining agent, the density of the slurry is reduced, thereby solving the problem of segment floating well; The present application adopts sodium α-olefin sulfonate and cocoamide succinate as air-entraining agents, which can cooperate with each other to effectively reduce the surface tension of water and generate a very large number of stable tiny bubbles, which can effectively reduce the density of grouting slurry and save cement. The air-entraining agent in the present application is rich in anions. After it is added together with cement, sand and water, the cement particles immediately adsorb anions and become negatively charged, so that the water around the cement particles becomes polarized and like ions repel each other, thereby preventing adjacent ions of the cement particles from approaching each other, achieving the effect of dispersion and separation, and improving the adsorption and diffusion capacity of the cement particles, thereby inhibiting the generation of agglomerates in the cement mortar, increasing the contact area between the cement particles and water, and allowing the cement particles to be fully hydrolyzed and hydrated. At the same time, during the diffusion process of cement particles, free water surrounded by the agglomerates is released, and the cement mortar changes from a network agglomerate structure to a sol structure, which makes the mortar have good water retention and viscosity, thereby improving the fluidity and workability of the mortar. In addition, due to the addition of air entraining agent, the density of the grouting slurry decreases, and the compressive strength of the grouting slurry also decreases after solidification. However, since the present application uses sodium α-olefin sulfonate and cocoamide succinate as air entraining agents, the cement particles are fully hydrolyzed and hydrated, which makes up for the lost compressive strength, so that the grouting slurry used in the present application still has good compressive performance after solidification.
[0007] Preferably, the mass ratio of the sodium α-olefin sulfonate to cocoamido succinate sulfonate is (3-5.7):1.
[0008] Preferably, the mass ratio of the sodium α-olefin sulfonate to cocoamido succinate sulfonate is 4:1.
[0009] By adopting the above technical scheme, the sodium α-olefin sulfonate and cocoamide succinate sulfonate within the above mass range can better play a cooperative role, and the generated bubbles are richer and more stable, which can further improve the fluidity of the grouting slurry, reduce the density of the grouting slurry, and reduce the amount of cement used.
[0010] Preferably, the invention further comprises 0.3-0.5 parts by weight of an auxiliary agent, wherein the auxiliary agent comprises glutaconic acid and sodium carboxymethyl cellulose.
[0011] Preferably, the mass ratio of the glutaconic acid to sodium carboxymethyl cellulose is 2:1.
[0012] By adopting the above technical solution, during the stirring process, the glutaric acid polymer molecules are arranged on the gas-liquid interface to form a stable bubble film, with the hydrophilic end facing the water and the hydrophobic end facing the air. This arrangement reduces the possibility of bubble merging and maintains the stability of the bubbles. Therefore, the glutaric acid promotes the air entraining agent to be evenly distributed and of appropriate size in the grouting slurry, and the sodium carboxymethyl cellulose can increase the bubble wall thickness and increase the viscosity of the liquid phase medium, which helps to enhance the stability of the bubbles, so that the bubbles can be stably present in the concrete during the parking and vibration of the grouting slurry without aggregation and dissipation. The two are used in combination to further enhance the stability of the bubbles from different angles, reduce the direct rupture of the bubbles during the stirring process or the rupture due to aggregation and enlargement; and when the mass ratio of glutaric acid and sodium carboxymethyl cellulose is 2:1, the two can play a better coordination effect and the bubble stability is better.
[0013] Preferably, 0.4-0.8 parts by weight of nano-enhanced particles are also included.
[0014] Preferably, the nano-reinforced particles are nano-silicon dioxide.
[0015] By adopting the above technical scheme, nano-reinforced particles are introduced into the air-entraining agent liquid. The nano-reinforced particles can be adsorbed on the gas-liquid interface of the bubbles to produce a "particle skeleton" and form a dense "particle-reinforced film", which can effectively inhibit the aggregation and disproportionation between bubbles. In addition, the adsorption energy of nano-silicon dioxide in the bubble film is relatively large, and it is difficult to desorb when adsorbed on the gas-liquid interface of the bubbles.
[0016] In a second aspect, the present application provides a method for preparing a cement-based shield synchronous grouting material, which adopts the following technical solution: A method for preparing a cement-based shield synchronous grouting material comprises the following steps: S1: adding air-entraining agent into water and stirring to obtain a mixed solution; S2: Add cement, sand, fly ash and bentonite into a mixer and stir evenly to obtain dry material; S3: Mix the mixed liquid and dry material, stir evenly, and obtain cement-based shield synchronous grouting material.
[0017] By adopting the above technical scheme, the cement-based shield synchronous grouting material prepared through the above preparation steps has good fluidity, high air content and low cement content.
[0018] In summary, this application has the following beneficial effects: 1. This application uses sodium α-olefin sulfonate and cocoamide succinate as air entraining agents. The two cooperate with each other to significantly reduce the density of the slurry, and can also significantly improve the fluidity and gas content of the grouting slurry, reduce the loss of consistency over time, and the compressive strength remains almost unchanged. It also effectively reduces the amount of grouting required for each ring, saving more than 0.35m of slurry per ring.3 , thus saving cement and reducing carbon emissions; and, due to the reduced density of the grouting slurry, the problem of the pipe segments floating up is well solved; 2. This application uses glutaric acid and sodium carboxymethyl cellulose. Glutaric acid promotes the uniform distribution and appropriate size of the air entraining agent in the grouting slurry. Sodium carboxymethyl cellulose can increase the bubble wall thickness and increase the viscosity of the liquid medium, which helps to enhance the stability of the bubbles. The two are used in combination to reduce the direct rupture of bubbles during stirring or the rupture due to aggregation and enlargement.
[0019] 3. The present application also introduces nano-reinforced particles into the grouting slurry. The nano-reinforced particles effectively inhibit the aggregation and disproportionation between bubbles, can reduce the rupture of bubbles due to aggregation, and enhance the stability of bubbles.
[0020] Source of raw materials The cement was P·O42.5 ordinary Portland cement produced by Tangshan Hongtai Cement Co., Ltd.; The fly ash comes from the Class II fly ash produced by Tianjin Guodian Jinneng Thermal Power Co., Ltd.; The bentonite comes from sodium-based bentonite produced by Hongli Active Bentonite Factory in Fangzi District, Weifang City; The sand comes from river sand with a fineness modulus of 1.4; Sodium α-olefin sulfonate was from Shandong Yousuo Chemical, product number: S11202215; Cocoamidosuccinate was from Chongqing Ruiya Biotechnology Co., Ltd., product number: 61791-66-0; Glutaric acid was from Wuhan Xinweiye Chemical Co., Ltd. with a purity of 98%; Sodium rosinate was obtained from Guangdong Wengjiang Chemical Reagent Co., Ltd., product number: PA30227; Sodium alkylbenzene sulfonate was obtained from Hubei Kewode Chemical Co., Ltd. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments. Example
[0022] Example 1 The preparation method of cement-based shield synchronous grouting material comprises the following steps: S1: 0.5 kg of air entraining agent (0.375 kg of sodium α-olefin sulfonate and 0.125 kg of cocoamido succinate) was added to 330 kg of water and stirred at 500 r / min for 60 min to obtain a mixed solution; S2: 170kg cement, 760kg sand, 240kg fly ash and 50kg bentonite are added to a mixer, stirred to obtain dry material; S3: The obtained mixed liquid and dry material are completely mixed and stirred evenly to obtain a cement-based shield synchronous grouting material.
[0023] Example 2 The preparation method of cement-based shield synchronous grouting material comprises the following steps: S1: 1 kg of air-entraining agent (0.75 kg of sodium α-olefin sulfonate and 0.25 kg of cocoamido succinate) was added to 350 kg of water and stirred at 600 r / min for 50 min to obtain a mixed solution; S2: 180kg cement, 770kg sand, 250kg fly ash and 55kg bentonite are added into a mixer, stirred to obtain dry material; S3: The obtained mixed liquid and dry material are completely mixed and stirred evenly to obtain a cement-based shield synchronous grouting material.
[0024] Example 3 The preparation method of cement-based shield synchronous grouting material comprises the following steps: S1: 2 kg of air-entraining agent (1.5 kg of sodium α-olefin sulfonate and 0.5 kg of cocoamido succinate) was added to 370 kg of water and stirred at 650 r / min for 45 min to obtain a mixed solution; S2: 190kg cement, 780kg sand, 260kg fly ash and 60kg bentonite are added to a mixer, stirred to obtain dry material; S3: The obtained mixed liquid and dry material are completely mixed and stirred evenly to obtain a cement-based shield synchronous grouting material.
[0025] Example 4 The difference between Example 4 and Example 2 is that the addition amount of sodium α-olefin sulfonate is 0.8 kg, the addition amount of cocoamide succinate is 0.2 kg, the mass ratio of the two is 4:1, and the remaining steps are the same as in Example 2.
[0026] Example 5 The difference between Example 5 and Example 2 is that the addition amount of sodium α-olefin sulfonate is 0.7 kg, the addition amount of cocoamide succinate is 0.3 kg, the mass ratio of the two is about 5.7:1, and the remaining steps are the same as Example 2.
[0027] Example 6 The difference between Example 6 and Example 2 is that the addition amount of sodium α-olefin sulfonate is 0.9 kg, the addition amount of cocoamide succinate is 0.1 kg, the mass ratio of the two is about 9:1, and the remaining steps are the same as in Example 2.
[0028] Example 7 The difference between Example 7 and Example 2 is that the addition amount of sodium α-olefin sulfonate is 0.7 kg, the addition amount of cocoamide succinate is 0.3 kg, the mass ratio of the two is about 2.3:1, and the remaining steps are the same as in Example 2.
[0029] Example 8 The difference between Example 8 and Example 4 is that 0.3 kg of auxiliary agent is further added in step S1, and the auxiliary agent includes 0.15 kg of glutaconic acid and 0.15 kg of sodium carboxymethyl cellulose, and the remaining steps are the same as those in Example 4.
[0030] Example 9 The difference between Example 9 and Example 4 is that 0.4 kg of auxiliary agent is further added in step S1, and the auxiliary agent includes 0.2 kg of glutaconic acid and 0.2 kg of sodium carboxymethyl cellulose, and the remaining steps are the same as those in Example 4.
[0031] Example 10 The difference between Example 10 and Example 4 is that 0.5 kg of auxiliary agent is further added in step S1, and the auxiliary agent includes 0.25 kg of glutaconic acid and 0.25 kg of sodium carboxymethyl cellulose, and the remaining steps are the same as Example 4.
[0032] Embodiment 11 The difference between Example 11 and Example 9 is that the amount of glutaconic acid added is 0.27 kg, the amount of sodium carboxymethyl cellulose added is 0.13 kg, the mass ratio of the two is about 2:1, and the remaining steps are the same as Example 9.
[0033] Example 12 The difference between Example 12 and Example 9 is that the added amount of glutaconic acid is 0.3 kg, the added amount of sodium carboxymethyl cellulose is 0.1 kg, the mass ratio of the two is about 3:1, and the remaining steps are the same as Example 9.
[0034] Embodiment 13 The difference between Example 13 and Example 11 is that 0.4 kg of nano-reinforced particles are further added in step S1, and the nano-reinforced particles are nano-silicon dioxide. The remaining steps are the same as Example 11.
[0035] Embodiment 14 The difference between Example 14 and Example 11 is that 0.6 kg of nano-reinforced particles are further added in step S1, and the nano-reinforced particles are nano-silicon dioxide. The remaining steps are the same as Example 11.
[0036] Embodiment 15 The difference between Example 15 and Example 11 is that 0.8 kg of nano-reinforced particles are further added in step S1, and the nano-reinforced particles are nano-silicon dioxide. The remaining steps are the same as Example 11.
[0037] Example 16 The difference between Example 16 and Example 15 is that the nano-reinforced particles are nano-titanium dioxide, and the remaining steps are the same as Example 15.
[0038] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no air entraining agent is added, and the remaining steps are the same as those of Example 1.
[0039] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that all the sodium α-olefin sulfonate is replaced by an equal amount of cocoamido succinate, and the remaining steps are the same as those of Example 1.
[0040] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that all cocoamido succinate is replaced by an equal amount of sodium α-olefin sulfonate, and the remaining steps are the same as those of Example 1.
[0041] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the sodium α-olefin sulfonate is replaced by an equal amount of sodium rosin acid, and the remaining steps are the same as those of Example 1.
[0042] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that all cocoamide succinate is replaced by an equal amount of sodium rosin acid, and the remaining steps are the same as those of Example 1.
[0043] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the air entraining agent is replaced by an equal amount of sodium alkylbenzene sulfonate, and the remaining steps are the same as those of Example 1.
[0044] Performance testing Detection Methods Referring to JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", the apparent density, air content, consistency and 2h consistency loss over time of cement-based shield synchronous grouting materials of Examples 1-16 and Comparative Examples 1-6 were tested, as well as the compressive strength test after 28 days of curing; According to the statistical analysis of the grouting data at the construction site, taking a municipal drainage shield tunnel currently under construction in Binhai as an example, the tunnel is made up of multiple ring segments, each with an inner diameter of 3m, an outer diameter of 3.5m, and a ring sink of 1.2m. Conventional synchronous grouting materials are used, and the final synchronous grouting pressure is set to 300kPa, and the grouting volume of each ring is calculated. The specific test results are shown in the following table: Table 1 Performance test of cement-based shield synchronous grouting materials of Examples 1-16 and Comparative Examples 1-6 Combining the data of Examples 1-3, Comparative Example 1 and Table 1, it can be seen that adding air entraining agent to the grouting slurry can reduce the slurry density from 1920kg / m3 to 1710kg / m3, and can also significantly improve the fluidity and gas content of the grouting slurry, reduce the time-dependent loss of consistency, and keep the compressive strength almost unchanged. It can also effectively reduce the grouting amount required for each ring, saving 0.35m3 of slurry per ring. 3 , thereby saving cement and reducing carbon emissions.
[0045] Combined with the data of Example 2, Examples 4-7 and Table 1, it can be seen that when the mass ratio of sodium α-olefin sulfonate and cocoamido succinate is (3-5.7): 1, sodium α-olefin sulfonate and cocoamido succinate can better play a cooperative role, and the generated bubbles are rich and stable, which can further improve the fluidity of the grouting slurry, reduce the time-dependent loss of consistency, reduce the density of the grouting slurry, and reduce the amount of cement used.
[0046] Combined with the data in Example 4, Examples 8-12 and Table 1, it can be seen that the addition of glutaric acid and sodium carboxymethyl cellulose in step S1 can further enhance the stability of the bubbles from different angles, avoid the bubbles from directly bursting during the slurry stirring process or bursting due to aggregation, thereby further improving the fluidity of the grouting slurry, reducing the time-dependent loss of consistency, reducing the density of the grouting slurry, and reducing the amount of cement used. When the mass ratio of glutaric acid and sodium carboxymethyl cellulose is 2:1, the two can play a better coordination effect and be added to the grouting slurry, so that the performance of the grouting slurry is slightly better.
[0047] Combining the data of Example 11, Examples 13-16 and Table 1, it can be seen that adding nano-silicon dioxide in step S1 can further prevent bubble rupture caused by bubble aggregation, thereby further improving the stability of the bubbles and the overall performance of the grouting slurry. From the data, the compressive resistance of the solidified grouting slurry is slightly improved, which may be due to the fact that some nanoparticles fill the gaps between the cement, enhancing its compressive resistance.
[0048] Combined with the data in Example 1, Comparative Examples 1-6 and Table 1, the present application adopts sodium α-olefin sulfonate and cocoamide succinate as air entraining agents, and the two can cooperate with each other to form abundant and stable bubbles, thereby improving the fluidity and air content of the mortar, reducing the density of the grouting slurry, and the compressive strength of the grouting slurry remains basically unchanged after curing.
[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A cement-based shield synchronous grouting material, characterized in that: The invention comprises the following raw materials in parts by weight: 170-190 parts of cement, 760-780 parts of sand, 240-260 parts of fly ash, 50-60 parts of bentonite, 330-370 parts of water and 0.5-2 parts of air entraining agent, wherein the air entraining agent comprises sodium alpha-olefin sulfonate and cocoamido succinate sulfonate.
2. A cement-based shield synchronous grouting material according to claim 1, characterized in that: The mass ratio of the sodium α-olefin sulfonate to cocoamide succinate sulfonate is (3-5.7):
1.
3. A cement-based shield synchronous grouting material according to claim 2, characterized in that: The mass ratio of the sodium α-olefin sulfonate to cocoamido succinate sulfonate is 4:
1.
4. The cement-based shield synchronous grouting material according to claim 1, characterized in that: The invention also comprises 0.3-0.5 parts by weight of auxiliary agents, wherein the auxiliary agents comprise glutaconic acid and sodium carboxymethyl cellulose.
5. The cement-based shield synchronous grouting material according to claim 4, characterized in that: The mass ratio of the glutaconic acid to sodium carboxymethyl cellulose is 2:
1.
6. The cement-based shield synchronous grouting material according to claim 4, characterized in that: Also included is 0.4-0.8 parts by weight of nano-reinforced particles.
7. The cement-based shield synchronous grouting material according to claim 6, characterized in that: The nano-enhanced particles are nano-silicon dioxide.
8. A method for preparing the cement-based shield synchronous grouting material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: adding air-entraining agent into water and stirring to obtain a mixed solution; S2: Add cement, sand, fly ash and bentonite into a mixer and stir evenly to obtain dry material; S3: Mix the mixed liquid and dry material, stir evenly, and obtain cement-based shield synchronous grouting material.
Citation Information
Patent Citations
Air entraining agent for concrete
CN106116221A
Uniform bleeding-free micro-expansion shield synchronous grouting material and preparation method thereof
CN111170700A
Concrete air entraining agent as well as preparation and application thereof
CN112062500A
Special foaming agent for light cement base and preparation method thereof
CN114477833A
Shield grouting material and preparation method thereof
CN114573278A